Defferentiated gender ownership of cassava fields and implications for root yield variations in small holder agriculture of southeast Nigeria - Enete, A.A.; Nweke, F.I.; Achike, A.I.; Tollens, E. (2001)
As a result of their relatively limited access to production resources, it has been variously reported that women obtain lower yields from their individual crop fields than men. Cassava root yields obtained from farmers' fields in three villages of southeast Nigeria were compared using separate ownership of fields by gender as a factor. The result of the analysis fails to confirm lower yields from women's fields. Instead, mean fresh root yield was lower for fields owned individually by men than for those owned individually by women, and about the same for fields owned jointly by the whole family and those owned individually by women. This was apparently because of differences in the use of purchased inputs, especially hired labor and improved cassava varieties, and perhaps also due to differences in the age of cassava at harvest and the intercropping of cassava as a minor crop with yam.